Choline Attenuates Cardiac Fibrosis by Inhibiting p38MAPK Signaling Possibly by Acting on M3 Muscarinic Acetylcholine Receptor - Zhao, Lihui; Chen, Tingting; Hang, Pengzhou; Li, Wen; Guo, Jing; Pan, Yang; Du, Jingjing; Zheng, Yuyang; Du, Zhimin (Frontiers in Pharmacology, 2019)
Choline has been reported to produce a variety of cellular functions including cardioprotection via activating M3 muscarinic acetylcholine receptor (M3R) under various insults. However, whether choline offers similar beneficial effects via the same mechanism in cardiac fibrosis remained unexplored. The present study aimed to investigate the effects of choline on cardiac fibrosis and the underlying signaling mechanisms, particularly the possible involvement of M3R. Transverse aortic constriction (TAC) mouse model was established to simulate the cardiac fibrosis. Transforming growth factor (TGF)-β1 treatment was employed to induce proliferation of cardiac fibroblasts in vitro. Choline chloride and M3R antagonist 4-diphenylacetoxy-N-methylpiperidine methiodide (4-DAMP) were used to unravel the potential role of M3R. Cardiac function was assessed by echocardiography and interstitial fibrosis was quantified by Masson staining. Protein levels of collagens I and III were determined by Western blot analysis. The role of M3R in the proliferation cardiac fibroblasts was validated by silencing M3R with specific small interference RNA (siRNA). Furthermore, the mitogen-activated protein kinase (MAPK) signaling pathway including p38MAPK and ERK1/2 as well as the TGF-β1/Smad pathway were analyzed. M3R protein was found abundantly in cardiac fibroblasts. M3R protein level, as identified by Western blotting, was higher in mice with excessive cardiac fibrosis and in TGF-β1-induced cardiac fibrosis as well. Choline significantly inhibited interstitial fibrosis, and this beneficial action was reversed by 4-DAMP. Production of collagens I and III was reduced after choline treatment but restored by 4-DAMP. Expression silence of endogenous M3R using siRNA increased the level of collagen I. Furthermore, the TGF-β1/Smad2/3 and the p38MAPK pathways were both suppressed by choline. In summary, choline produced an anti-fibrotic effect both in vivo and in vitro by regulating the TGF-β1/Smad2/3 and p38MAPK pathways. These findings unraveled a novel pharmacological property of choline linked to M3R, suggesting that choline regulates cardiac fibrosis and the associated heart diseases possibly by acting on M3R.